Known Unknowns and Unknown Knowns: What we know about the cannabis and the Hashish trade in Afghanistan - James Bradford; David Mansfield (EchoGéo)
In the past four decades, much of the contemporary narrative of Afghanistan has been defined by opium. However, underneath the veil of the opium economy, the cannabis trade remains an enduring component of Afghanistan’s political economy and culture. Much of this stems from the long history of cannabis cultivation and hashish production in the region. During the 1960s, the growing demand from Western nations for Afghan hashish helped forge key global trafficking networks, as well as significant changes to the cultivation of cannabis and production of hashish. Since then, production and trade evolved, with cultivation of cannabis more widespread. Ultimately, analyzing the cannabis trade and its historical antecedents, reveals how the cannabis trade, like the opium economy, transformed in response to local, regional, and global factors, remaining an important piece of the rural Afghan economy today.